Comparative Anatomical Study of the Eye in Three Different Birds - Taha, Ameer M.; Hamid, Hamid Hassan (International Journal of Scientific Research in Biological Sciences, 2020)
The present study investigated the comparative anatomy of the eye in three types of birds that differ in the nature, environment and categories. These birds are the Eurasian sparrowhawk Accipiter nisus (from carnivores), the Common starling Sturnus vulgaris (from omnivorous) and the spotted sparrow Taeniopygia guttata (from Grainivorous). The results showed that the eye in three types of the birds was spherical or semi-spherical . In sparrowhawk, however, is larger than the other two types in terms of size. In the starling is larger than the spotted sparrow relative to the size of the body. The eye is located on the sides of the head in the three birds, but in different position. The basic structure of the eyeball in the three types is relatively similar, and appeared to consist of three tunics: the fibrous tunic (the sclera) altered at the front of the cornea, the second tunica is the Uvea which contains three parts including choroid, the ciliary body and iris, while the third tunic is the retina. , in addition number of structures that do not belong to any of the previous tunics, they are the lens, optic nerve, and pectin oculi. The iris located behind the cornea with an orange color appeared in the sparrowhawk and with a black color in the starling, while in the spotted sparrow was a dark brown color, as the area of the optic nerve exit from the eye differed in the three birds.